Comparison of the Ultrasonic Evaluation of Bi-Parietal Diameter and Femoral Length in 2nd and 3rd Trimester to Estimate the Gestational Age (Bangladesh Medical Journal, 2021)
During the gestational period, fetal biometrics are assessed through ultrasonography to observe the growth of the fetus. This study observed the corresponding of gestational age those were measured by two of the fetal diameters; gestational age were calculated from history of last menstrual period (LMP), in the last two trimesters. This descriptive type of observational study was carried out in the Department of Radiology and Imaging of Dhaka Medical College and Hospital, during the period of July, 2004 to June, 2005. Here 291 single-ton, non-complicated pregnant women of LMP were selected purposively from valid record. Bi-parietal diameter (BPD) and femoral length (FL) estimated through ultrasonography. These two parameters compared with the gestational age in second and third trimester. The study found that, before 36th week, the BPD based gestational age varied 2 to 3 days from LMP based gestational age and after that, the variation was 1 to 4 weeks. In case of FL, the ultrasonic measurement found to be 2 to 4 days backward in the second trimester and 2 to 3 days advance in the last trimester in contrast to the LMP based gestational age. In the second trimester, it has been found that, BPD has been the superior predictor of the gestational age than the FL with the correlation coefficient of 0.999 in case of BPD and 0.998 in case of FL when correlated with LMP based gestational age. Although, in third trimester, FL versus BPD predicted the gestational age with a correlation coefficient of 0.998 versus 0.978 respectively, when correlated with gestational age based on the history of LMP. This study has observed that, later in pregnancy, FL has the better predictability over BPD to determine the gestational age.Bangladesh Med J. 2020 Sept; 49(3) : 43-48